2019
DOI: 10.21037/tau.2018.10.19
|View full text |Cite
|
Sign up to set email alerts
|

The rational and benefits of the second look transurethral resection of the bladder for T1 high grade bladder cancer

Abstract: The second look transurethral resection of the bladder (TURB) represents a fundamental step in the treatment of papillary non-muscle invasive bladder cancer (NMIBC); it is therefore recommended by all guidelines. However, not all the literature agrees on its staging value and its ability to improve oncological outcomes of patients. Therefore, the purpose of this review is to evaluate the strengths and weaknesses of second look TURB, trying to depict its evolving role in the management of high grade NMIBC. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 59 publications
2
15
1
1
Order By: Relevance
“…Transurethral resection with intravesical therapy is the first-line therapy for patients with NMIBC (11). However, recurrence or progression occurs in more than half of all patients, which requires a second resection or cystectomy (3840). Therefore, the overall situation and the prognosis of the patient must be taken into account when selecting the most appropriate surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Transurethral resection with intravesical therapy is the first-line therapy for patients with NMIBC (11). However, recurrence or progression occurs in more than half of all patients, which requires a second resection or cystectomy (3840). Therefore, the overall situation and the prognosis of the patient must be taken into account when selecting the most appropriate surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the presence of detrusor muscle on initial TUR reduces the benefits of a re-TUR, even more so when patient's quality of life and healthcare costs come into play. 17,18 A retrospective analysis showed that time to recurrence for high-grade TCC after the first resection was significantly shorter compared to those who underwent re-TUR (median = 22 months vs 36 months, p < 0.001). Failure to perform a repeat resection prior to initiation of intravesical BCG therapy for high-risk NMIBC significantly increases the risk of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the presence of detrusor muscle on initial TUR reduces the benefits of a re-TUR, even more so when patient’s quality of life and healthcare costs come into play. 17,18…”
Section: Discussionmentioning
confidence: 99%
“…The surgical treatment includes transurethral resection of bladder tumor, transurethral laser surgery, and photodynamic therapy. TURBT is the current "gold standard" for the treatment of NMIBC and also the main treatment [17][18][19]. The objectives of TURBT are as follows: first, complete removal of all tumors within the field of vision to achieve the effect of radical surgical resection; second, resection of tissues for evaluation of pathological grade and stage, determination of the next postoperative treatment plan of the patient, and assessment of prognosis and risk of recurrence.…”
Section: Discussionmentioning
confidence: 99%